Aids for people with alzheimer’s disease or other dementia II - Mok, Wei Jie. (2013)
The Alzheimer’s Disease is the most common cause of dementia among the elderly. The disease is an irreversible and progressive brain disease that slowly destroys the memory and thinking abilities. Scientists do not yet have the answer to cure the Alzheimer’s disease but the research focus have shown that people who maintain active cognition will delay the symptoms of the disease.